Tanggung Jawab Jabatan dan Tanggung Jawab Pribadi Dalam Penggunaan Diskresi - Adam Setiawan; Nehru Asyikin (Universitas Muhammadiyah Purwokerto, 2020)
Discretion is part of the authority to act freely by government officials to ensure the implementation of public services. However, the discretionary arrangement attached to a position when it must be immediately acted without a written law creates a conflict regarding the government must be based on law. On the other hand, the need for discretion becomes a polemic regarding occupational responsibility and personal responsibility in the use of discretion whose parameters sometimes cause harm to society. The results of this research are of interest that the implications of using official diskettes for public services will cause harm to the state and society. The use of discretion is used as a tool for personal gain and authority which results in violating statutory regulations, contrary to legal principles, acts against the law, and AAUPB.Keywords: discretion, job responsibility, personal responsibility